2018
DOI: 10.1111/ejn.13857
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic activity layer specifically modulates synaptic potentiation in the mouse insular cortex

Abstract: Nicotinic acetylcholine receptors (nAChRs) in the insular cortex play an important role in nicotine addiction, but its cellular and synaptic mechanisms underlying nicotine addiction still remain unresolved. In layer 5 pyramidal neurons of the mouse insular cortex, activation of nAChRs suppresses synaptic potentiation through enhancing GABAergic synaptic transmission via activation of β2-containing nAChRs in non-fast-spiking (non-FS) interneurons. However, it has not been addressed whether and how activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
6
10
0
Order By: Relevance
“…In agreement with these findings, most of L3 PCs in the IC (26 of 29 cells, 90%) did not have functional nicotinic receptors ( Figure 1) [21]. Indeed, glutamatergic synaptic transmission in L3 PCs of the IC was not affected by nicotinic receptor activation [21]. In L3 of the IC, an about half of fast-spiking interneurons (6 of 11 cells, 55%) expressed α7 nicotinic receptors and most of non-fast-spiking interneurons expressed α7 and/or β2 nicotinic receptors (α7/β2: 11 of 28 cells; 39%, α7: 5 of 28 cells; 18%, β2: 10 of 28 cells; 36%, Figure 1) [21].…”
Section: Layer-dependent Modulation Of Synaptic Transmission By Nicotsupporting
confidence: 85%
See 2 more Smart Citations
“…In agreement with these findings, most of L3 PCs in the IC (26 of 29 cells, 90%) did not have functional nicotinic receptors ( Figure 1) [21]. Indeed, glutamatergic synaptic transmission in L3 PCs of the IC was not affected by nicotinic receptor activation [21]. In L3 of the IC, an about half of fast-spiking interneurons (6 of 11 cells, 55%) expressed α7 nicotinic receptors and most of non-fast-spiking interneurons expressed α7 and/or β2 nicotinic receptors (α7/β2: 11 of 28 cells; 39%, α7: 5 of 28 cells; 18%, β2: 10 of 28 cells; 36%, Figure 1) [21].…”
Section: Layer-dependent Modulation Of Synaptic Transmission By Nicotsupporting
confidence: 85%
“…It has been demonstrated that a majority of L2/3 PCs in the PFC, visual cortex, somatosensory cortex and motor cortex do not have functional nicotinic receptors [14,[18][19][20]. In agreement with these findings, most of L3 PCs in the IC (26 of 29 cells, 90%) did not have functional nicotinic receptors ( Figure 1) [21]. Indeed, glutamatergic synaptic transmission in L3 PCs of the IC was not affected by nicotinic receptor activation [21].…”
Section: Layer-dependent Modulation Of Synaptic Transmission By Nicotsupporting
confidence: 61%
See 1 more Smart Citation
“…Therefore, the modulation of dopamine and other monoamine release caused by the activation of nAChRs may contribute to the nicotine‐induced inhibition of synaptic potentiation. In the mouse agranular insular cortex, nicotine‐induced modulation of synaptic plasticity is layer‐specific: nicotine suppresses synaptic potentiation in layers 3 and 5 pyramidal neurons while it facilities synaptic potentiation in layer 6 pyramidal neurons (Sato et al, ; Toyoda, ). Thus, future studies would be necessary to demonstrate how the interaction between nAChRs and dopamine receptors modulates synaptic plasticity in layers 3 and 6 pyramidal neurons of the insular cortex.…”
Section: Discussionmentioning
confidence: 99%
“…); cortex (Torterolo et al . , Toyoda ), hippocampus (Betterton et al . , laterodorsal tegmental nucleus (Taoka et al .…”
Section: Editors’ Notementioning
confidence: 99%